RETRACTED: Motivasi Belajar siswa SMK N 1 Payakumbuh dalam Pembelajaran Renang - Endi Ahmad; James Tangkudung; Yasep Setia Karna Wijaya; Widiastuti (Journal Sport Area)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is that this article also published in the Journal Physical Education, Health and Recreation